The Periodontal Management On T.I.A. Or Stroke Patient: A Case Report - Sorina Solomon; Liliana Pasarin; Alexandra Mârțu; Irina Ursarescu; Silvia Martu (Romanian Society of Oral Rehabilitation, 2013)
Besides carious lesions, periodontal infections are among the most frequent infections, both being determined by natural bacterial biofilms. In a manner of epidemiology, they manifest a strong social character, being present in all the human populations, in different age groups. There is a clear relation between the periodontal disease and other health problems, such as cardiovascular diseases, diabetes mellitus, and respiratory impairments. We present the case of a patient with generalized severe chronic marginal periodontitis and cerebrovascular accident (stroke), produced 3 months before his dental visit. There is a direct connection between the severe periodontal diseases, gingivitis and stroke, its potential rising in case of smoking or diabetes mellitus. The pathological mechanisms in periodontitis are associated with inflammation markers, risk indicators for stroke themselves. An early diagnosis and treatment of gingival-periodontal pathology can prevent the local and systemic complications of the periodontal disease.